PROMOSI KESEHATAN PADA ANAK SEKOLAH DASAR DALAM PENINGKATAN PENGETAHUAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS ) DI SD AL- IRSYAD KOTA BATU - Rahmadina, Sylvia Alda; Lala, Handy; Halis, Farida (Poltekkes Kemenkes Malang, 2023)
School children are one of the groups most vulnerable to health problems due to environmental factors and unfavorable lifestyles. This condition must be anticipated immediately by increasing a healthy lifestyle through PHBS. One of the efforts in health promotion to increase knowledge is to conduct health education regarding clean and healthy living behavior, especially in schools. The aim of this study was to determine the effect of health promotion on elementary school children in increasing knowledge of clean and healthy living behavior (PHBS) at Al-Irsyad Elementary School, Batu City. In this study the research method used was quantitative research using a Pre-Experimental Design or Pre-Experimental Design with the One Group Pretest Posttest Design approach. The sampling technique in this study was purposive sampling with inclusion and exclusion criteria. In this study, there were 34 children of grade 4 as samples. Based on the results of the study, it was shown that prior to being given health promotion they had sufficient knowledge with a percentage of 44.12% and less knowledge with a percentage of 55.88%, and after being given health promotion the respondents had good knowledge with a percentage of 100%. There is an effect of health promotion on increasing students' knowledge, based on the results of statistical tests showing 0.000 < 0.05, the hypothesis is accepted. The conclusion is that there is an effect of health promotion on knowledge of elementary school children regarding PHBS in grade IV students at Al-Irsyad Elementary School, Batu City.